The impact of the quality of gastronomic services on tourist satisfaction in agritourism farms in Eastern Serbia - Vukolić, Dragan; Gajić, Tamara; Knežević, Snežana; Cilić, Marko (Hotel and Tourism Management, 2024)
Purpose – The study aimed to analyze the quality of gastronomic services in the agrarian regions of Eastern Serbia, focusing on the experiences of tourists visiting these destinations. The research was motivated by the increasing importance of gastronomic services in contemporary studies, particularly in rural areas like Eastern Serbia, known for its unique offerings in agritourism. Methodology – The research was conducted in 2024 on a sample of 189 respondents across 14 agritourism farms in Eastern Serbia. Data were analyzed using SPSS software, version 26.00, and multiple regression analysis was employed to identify the key predictors influencing overall service quality. Findings – The results revealed a statistically significant impact of the quality of gastronomic services on tourist satisfaction. The analysis identified key predictors of the quality of gastronomic services that significantly contribute to the overall tourist experience, highlighting the importance of high-quality service in enhancing visitor satisfaction. Implications – The study’s findings contribute to the theoretical understanding of service quality in rural tourism and provide practical insights for agritourism operators in Eastern Serbia. By improving the quality of their gastronomic offerings, these operators can enhance tourist satisfaction and potentially increase visitor numbers.